Retromolar canal diagnosed by cone-beam computed tomography and its influence in inferior alveolar nerve block = Canal retromolar diagnosticado por tomografía computarizada de haz cónico y su influencia en el bloqueo del nervio alveolar inferior - Dantas Costa, Eliana da
The aim of this study was to observed the anesthetic efficacy of the alveolar nerve block on nine patients that CBCT diagnosed unilateral retromolar canal on a double-blind, split-mouth approach. The assessments of patient response to thermal (pulp vitality test) and pressure (compression of soft tissue) stimuli were carried out before and 5 minutes after the inferior alveolar nerve block procedure, using both visual analog scale (VAS) and Mc Gill pain questionnaires (McG). The mean percentage of patient response decreased after alveolar nerve block, according to both VAS and McG, and was statistically similar among hemi mandibles with and without retromolar canal (Wilcoxon>0.05); however, those without retromolar canal presented greater reduction in patient response in 6 out of 9 cases. Therefore, the retromolar canal is not a determinant factor of inferior alveolar nerve block failure.